Musical analyses and musical exegesis the shepherd's melody in Richard Wagner's Tristan and Isolde - Nattiez, Jean-Jacques 1945- (Eastman studies in music, 2021)
Here translated for the first time, Jean-Jacques Nattiez's widely hailed comparative guide to the techniques of music analysis focuses on a single vivid passage from Wagner's Tristan and Isolde